2021
DOI: 10.7759/cureus.12904
|View full text |Cite
|
Sign up to set email alerts
|

First Case of Dendriform Pulmonary Ossification in Bahrain

Abstract: Dendriform pulmonary ossification (DPO) is a rare interstitial lung disease characterised by the presence of mature bone with marrow elements in the lung parenchyma with typical radiologic findings of diffuse and numerous calcified nodules. In this case study, we are presenting a case of asymptomatic primary DPO discovered during routine screening chest X-ray. To our best knowledge, this is the first case of DPO reported in Bahrain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…Other secondary cases of DPO were observed in patients in their 60s–80s 32 33. However, recent reports have shown that IDPO diagnosed by surgical lung biopsy was distributed among patients in their 20s–40s 16–18 25–29. In our study, the diagnosis was made in 5 patients in their 20s and 8 patients in their 30s.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Other secondary cases of DPO were observed in patients in their 60s–80s 32 33. However, recent reports have shown that IDPO diagnosed by surgical lung biopsy was distributed among patients in their 20s–40s 16–18 25–29. In our study, the diagnosis was made in 5 patients in their 20s and 8 patients in their 30s.…”
Section: Discussioncontrasting
confidence: 59%
“…In addition, we did not ask the occupational exposure in detail, and did not extensively investigate the biomarkers including autoimmune markers. Although IDPO cases were often reported from Japan, some has been diagnosed in other countries such as Canada, 11 UK, 14 China, 16 Bahrain 17 and USA, 33 indicating that IDPO would be distributed worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Four cases were diagnosed by SLB because these patients could not be definitively diagnosed by TBLB. 2,[6][7][8] Thus, the diagnostic accuracy of TBLB for DPO, as well as in other interstitial lung diseases, may be controversial.…”
Section: Discussionmentioning
confidence: 99%